Hippocampal subfield plasticity is associated with improved spatial memory - Henning Boecker; Marcel Daamen; Lukas Kunz; Melanie Geiß; Moritz Müller; Thomas Neuss; Leonie Henschel; Rüdiger Stirnberg; Neeraj Upadhyay; Lukas Scheef; Jason A. Martin; Tony Stöcker; et al. (Communications Biology, 2024)

Cortical Amyloid Burden Relates to Basal Forebrain Volume in Subjective Cognitive Decline - Marcel Daamen; Lukas Scheef; Shumei Li; Michel J. Grothe; Florian C. Gaertner; Ralph Buchert; Katharina Buerger; Laura Dobisch; Alexander Drzezga; Markus Essler; Michael Ewers; Klaus Fliessbach; et al. (Journal of Alzheimer's Disease, 2023)

MRgFUS of the nucleus ventralis intermedius in essential tremor modulates functional connectivity within the classical tremor network and beyond - Christine Kindler; Neeraj Upadhyay; Veronika Purrer; Frederic Carsten Schmeel; Valeri Borger; Lukas Scheef; Ullrich Wüllner; Henning Boecker (Parkinsonism & related disorders : official journal of the World Federation of Neurology Research Committee on Parkinsonism and Related Disorders, 2023)

Physical Activity Alters Functional Connectivity of Orbitofrontal Cortex Subdivisions in Healthy Young Adults : A Longitudinal fMRI Study - Jannik Claus; Neeraj Upadhyay; Angelika Maurer; Julian Klein; Lukas Scheef; Marcel Daamen; Jason Anthony Martin; Rüdiger Stirnberg; Alexander Radbruch; Ulrike Attenberger; Tony Stöcker; Henning Boecker (Healthcare, 2023)

Coherent Structural and Functional Network Changes after Thalamic Lesions in Essential Tremor - Emily D.R. Pohl; Neeraj Upadhyay; Xenia Kobeleva; Veronika Purrer; Angelika Maurer; Vera C. Keil; Christine Kindler; Valeri Borger; Claus C. Pieper; Simon Groetz; Lukas Scheef; Jaroslaw Maciaczyk; et al. (Movement Disorders : official journal of the Movement Disorder Society, 2022)

Effects of a 6-Month Aerobic Exercise Intervention on Mood and Amygdala Functional Plasticity in Young Untrained Subjects - Angelika Maurer; Julian Klein; Jannik Claus; Neeraj Upadhyay; Leonie Henschel; Jason Anthony Martin; Lukas Scheef; Marcel Daamen; Theresa Schörkmaier; Rüdiger Stirnberg; Tony Stöcker; Alexander Radbruch; et al. (International Journal of Environmental Research and Public Health : IJERPH, 2022)

Regional cortical perfusion increases induced by a 6-month endurance training in young sedentary adults - Neeraj Upadhyay; Theresa Schörkmaier; Angelika Maurer; Jannik Claus; Lukas Scheef; Marcel Daamen; Jason A. Martin; Rüdiger Stirnberg; Alexander Radbruch; Ulrike Attenberger; Tony Stöcker; Henning Boecker (Frontiers in Aging Neuroscience, 2022)

Abnormal Regional and Global Connectivity Measures in Subjective Cognitive Decline Depending on Cerebral Amyloid Status - Shumei Li; Marcel Daamen; Lukas Scheef; Florian C. Gaertner; Ralph Buchert; Martina Buchmann; Katharina Buerger; Cihan Catak; Laura Dobisch; Alexander Drzezga; Birgit Ertl-Wagner; Markus Essler; et al. (Journal of Alzheimer's Disease, 2021)

Cortical representation of experimental periodontal pain : a functional magnetic resonance imaging study - Angelika Maurer; Damian Verma; Annika Reddehase; Lukas Scheef; Alexander Radbruch; Ulrike Attenberger; Andreas Jäger; Henning Boecker (Scientific Reports, 2021)

An analysis of MRI derived cortical complexity in premature-born adults: Regional patterns, risk factors, and potential significance - Dennis M. Hedderich; Josef G. Bäuml; Aurore Menegaux; Mihai Avram; Marcel Daamen; Claus Zimmer; Peter Bartmann; Lukas Scheef; Henning Boecker; Dieter Wolke; Christian Gaser; Christian Sorg (NeuroImage : a journal of brain function, 2020)

Decreased cortical thickness mediates the relationship between premature birth and cognitive performance in adulthood - Benita Schmitz‐Koep; Josef G. Bäuml; Aurore Menegaux; Rachel Nuttall; Juliana Zimmermann; Sebastian C. Schneider; Marcel Daamen; Lukas Scheef; Henning Boecker; Claus Zimmer; Christian Gaser; Dieter Wolke; et al. (Human brain mapping : a journal devoted to functional neuroanatomy and neuroimaging, 2020)

Hippocampal subfield volumes are nonspecifically reduced in premature‐born adults - Dennis M. Hedderich; Mihai Avram; Aurore Menegaux; Rachel Nuttall; Juliana Zimmermann; Sebastian C. Schneider; Benita Schmitz‐Koep; Marcel Daamen; Lukas Scheef; Henning Boecker; Claus Zimmer; Nicole Baumann; et al. (Human Brain Mapping, 2020)

Measuring plastic pellet (nurdle) abundance on shorelines throughout the Gulf of Mexico using citizen scientists: Establishing a platform for policy-relevant research - Jace W. Tunnell; Kelly H. Dunning; Lindsay P. Scheef; Kathleen M. Swanson (Marine pollution bulletin : the international journal for marine environmental scientists, engineers, administrators, politicians and lawyers, 2020)

MRI follow-up after magnetic resonance-guided focused ultrasound for non-invasive thalamotomy : the neuroradiologist’s perspective - Vera C. Keil; Valeri Borger; Veronika Purrer; Simon F. Groetz; Lukas Scheef; Henning Boecker; Hans H. Schild; Christine Kindler; Angelika Schmitt; Laszlo Solymosi; Ullrich Wüllner; Claus C. Pieper (Neuroradiology : a journal devoted to neuroimaging and interventional neuroradiology ; official organ of the European Society of Neuroradiology, 2020)

Prominent White Matter Involvement in Multiple System Atrophy of Cerebellar Type - Jennifer Faber; Ilaria Giordano; Xueyan Jiang; Christine Kindler; Annika Spottke; Julio Acosta‐Cabronero; Peter J. Nestor; Judith Machts; Emrah Düzel; Stefan Vielhaber; Oliver Speck; Ales Dudesek; et al. (Movement Disorders : official journal of the Movement Disorder Society, 2020)

Sequelae of Premature Birth in Young Adults - Dennis M. Hedderich; Tobias Boeckh-Behrens; Josef G. Bäuml; Aurore Menegaux; Marcel Daamen; Claus Zimmer; Peter Bartmann; Lukas Scheef; Henning Boecker; Dieter Wolke; Christian Sorg; Judith E. Spiro (Clinical neuroradiology : official publication of the German, Austrian and Swiss societies of neuroradiology, 2020)

Aberrant gyrification contributes to the link between gestational age and adult IQ after premature birth - Dennis M Hedderich; Josef G. Bäuml; Maria T. Berndt; Aurore Menegaux; Lukas Scheef; Marcel Daamen; Claus Zimmer; Peter Bartmann; Henning Boecker; Dieter Wolke; Christian Gaser; Christian Sorg (Brain : a journal of neurology, 2019)

Automated quantitative evaluation of brain MRI may be more accurate for discriminating preterm born adults - Alina Jurcoane; Marcel Daamen; Vera C. Keil; Lukas Scheef; Josef G. Bäuml; Chun Meng; Afra M. Wohlschläger; Christian Sorg; Barbara Busch; Nicole Baumann; Dieter Wolke; Peter Bartmann; et al. (European radiology : the official journal of the European Society of Radiology, 2019)

Characterization of Cerebellar Atrophy and Resting State Functional Connectivity Patterns in Sporadic Adult-Onset Ataxia of Unknown Etiology (SAOA) - Xueyan Jiang; J. Faber; I. Giordano; J. Machts; Ch. Kindler; A. Dudesek; O. Speck; Ch. Kamm; E. Düzel; F. Jessen; A. Spottke; St. Vielhaber; et al. (The Cerebellum, 2019)

Disentangling motor planning and motor execution in unmedicated de novo Parkinson's disease patients : An fMRI study - Jason A. Martin; Nadine Zimmermann; Lukas Scheef; Jakob Jankowski; Sebastian Paus; Hans H. Schild; Thomas Klockgether; Henning Boecker (NeuroImage : Clinical ; a journal of diseases affecting the nervous system ; open access journal, 2019)

Effects of low- and high-intensity exercise on emotional face processing : an fMRI face-matching study - Angelika Schmitt; Jason Anthony Martin; Sandra Rojas; Ramin Vafa; Lukas Scheef; Heiko Klaus Strüder; Henning Boecker (Social Cognitive and Affective Neuroscience, 2019)

Inter-ictal assay of peripheral circulating inflammatory mediators in migraine patients under adjunctive cervical non-invasive vagus nerve stimulation (nVNS) : A proof-of-concept study - Shafqat R. Chaudhry; Ilana S. Lendvai; Sajjad Muhammad; Philipp Westhofen; Johannes Kruppenbacher; Lukas Scheef; Henning Boecker; Dirk Scheele; Rene Hurlemann; Thomas M. Kinfe (Brain stimulation : basic, translational, and clinical research in neuromodulation, 2019)

Subregional volume reduction of the cholinergic forebrain in subjective cognitive decline (SCD) - Lukas Scheef; Michel J. Grothe; Alexander Koppara; Marcel Daamen; Henning Boecker; Hans Biersack; Hans H. Schild; Michael Wagner; Stefan Teipel; Frank Jessen (NeuroImage : Clinical ; a journal of diseases affecting the nervous system, 2019)

Executive control processes are associated with individual fitness outcomes following regular exercise training : blood lactate profile curves and neuroimaging findings - M. C. Pensel; M. Daamen; L. Scheef; H. U. Knigge; S. Rojas Vega; J. A. Martin; H. H. Schild; H. K. Strüder; H. Boecker (Scientific Reports, 2018)

The role of muscle strength on tendon adaptability in old age - D. Holzer; G. Epro; C. McCrum; J. Doerner; J. A. Luetkens; L. Scheef; G. M. Kukuk; H. Boecker; A. Mierau; G.-P. Brüggemann; C. N. Maganaris; K. Karamanidis (European Journal of Applied Physiology, 2018)

Functional Laterality of Task-Evoked Activation in Sensorimotor Cortex of Preterm Infants : An Optimized 3 T fMRI Study Employing a Customized Neonatal Head Coil - Lukas Scheef; Jurek A. Nordmeyer-Massner; Adam PR Smith-Collins; Nicole Müller; Gaby Stegmann-Woessner; Jacob Jankowski; Jürgen Gieseke; Mark Born; Hermann Seitz; Peter Bartmann; Hans H. Schild; Klaas P. Pruessmann; et al. (PLOS ONE, 2017)

Reduced Cholinergic Basal Forebrain Integrity Links Neonatal Complications and Adult Cognitive Deficits After Premature Birth - Michel J. Grothe; Lukas Scheef; Josef Bäuml; Chun Meng; Marcel Daamen; Nicole Baumann; Claus Zimmer; Stefan Teipel; Peter Bartmann; Henning Boecker; Dieter Wolke; Afra Wohlschläger; et al. (Biological psychiatry : a journal of psychiatric neuroscience ; a publication of the Society of Biological Psychiatry, 2017)

The Achilles tendon is mechanosensitive in older adults: adaptations following 14 weeks versus 1.5 years of cyclic strain exercise - Gaspar Epro; Andreas Mierau; Jonas Doerner; Julian A. Luetkens; Lukas Scheef; Guido M. Kukuk; Henning Boecker; Constantinos N. Maganaris; Gert-Peter Brüggemann; Kiros Karamanidis (Journal of Experimental Biology, 2017)

Central Pain Processing in Early-Stage Parkinson's Disease : A Laser Pain fMRI Study - Christine Petschow; Lukas Scheef; Sebastian Paus; Nadine Zimmermann; Hans H. Schild; Thomas Klockgether; Henning Boecker (PLOS ONE, 2016)

Cortical Thinning in Individuals with Subjective Memory Impairment - Dix Meiberth; Lukas Scheef; Steffen Wolfsgruber; Henning Boecker; Wolfgang Block; Frank Träber; Susanne Erk; Michael T. Heneka; Heike Jacobi; Annika Spottke; Henrik Walter; Michael Wagner; et al. (Journal of Alzheimer's Disease, 2015)

Extensive and interrelated subcortical white and gray matter alterations in preterm-born adults - C. Meng; J. G. Bäuml; M. Daamen; J. Jaekel; J. Neitzel; L. Scheef; B. Busch; N. Baumann; H. Boecker; C. Zimmer; P. Bartmann; D. Wolke; et al. (Brain Structure and Function, 2015)

Neural correlates of executive attention in adults born very preterm - Marcel Daamen; Josef G. Bäuml; Lukas Scheef; Chun Meng; Alina Jurcoane; Julia Jaekel; Christian Sorg; Barbara Busch; Nicole Baumann; Peter Bartmann; Dieter Wolke; Afra Wohlschläger; et al. (NeuroImage : Clinical ; a journal of diseases affecting the nervous system ; open access journal, 2015)

Visual attention in preterm born adults : Specifically impaired attentional sub-mechanisms that link with altered intrinsic brain networks in a compensation-like mode - Kathrin Finke; Julia Neitzel; Josef G. Bäuml; Petra Redel; Hermann J. Müller; Chun Meng; Julia Jaekel; Marcel Daamen; Lukas Scheef; Barbara Busch; Nicole Baumann; Henning Boecker; et al. (NeuroImage : a journal of brain function, 2015)

White matter alterations of the corticospinal tract in adults born very preterm and/or with very low birth weight - Alina Jurcoane; Marcel Daamen; Lukas Scheef; Josef G. Bäuml; Chun Meng; Afra M. Wohlschläger; Christian Sorg; Barbara Busch; Nicole Baumann; Dieter Wolke; Peter Bartmann; Elke Hattingen; et al. (Human Brain Mapping, 2015)

Correspondence Between Aberrant Intrinsic Network Connectivity and Gray-Matter Volume in the Ventral Brain of Preterm Born Adults - Josef G. Bäuml; Marcel Daamen; Chun Meng; Julia Neitzel; Lukas Scheef; Julia Jaekel; Barbara Busch; Nicole Baumann; Peter Bartmann; Dieter Wolke; Henning Boecker; Afra M. Wohlschläger; et al. (Cerebral Cortex, 2014)

Working memory in preterm‐born adults : Load‐dependent compensatory activity of the posterior default mode network - Marcel Daamen; Josef G. Bäuml; Lukas Scheef; Christian Sorg; Barbara Busch; Nicole Baumann; Peter Bartmann; Dieter Wolke; Afra Wohlschläger; Henning Boecker (Human Brain Mapping, 2014)

Abnormal Movement Preparation in Task-Specific Focal Hand Dystonia - Jakob Jankowski; Sebastian Paus; Lukas Scheef; Malte Bewersdorff; Hans H. Schild; Thomas Klockgether; Henning Boecker (PLoS ONE, 2013)

Gray matter atrophy pattern in elderly with subjective memory impairment - Jessica Peter; Lukas Scheef; Ahmed Abdulkadir; Henning Boecker; Michael Heneka; Michael Wagner; Alexander Koppara; Stefan Klöppel; Frank Jessen (Alzheimer's & dementia : the journal of the Alzheimer's Association, 2013)

Quantifying effects of abiotic and biotic drivers on community dynamics with multivariate autoregressive (MAR) models - Stephanie E. Hampton; Elizabeth E. Holmes; Lindsay P. Scheef; Mark D. Scheuerell; Stephen L. Katz; Daniel E. Pendleton; Eric J. Ward (Ecology : a publication of the Ecological Society of America, 2013)

An fMRI study on the acute effects of exercise on pain processing in trained athletes - Lukas Scheef; Jakob Jankowski; Marcel Daamen; Gunther Weyer; Markus Klingenberg; Julia Renner; Sara Mueckter; Britta Schürmann; Frank Musshoff; Michael Wagner; Hans H. Schild; Andreas Zimmer; et al. (Pain : the journal of the International Association for the Study of Pain, 2012)

Association of amygdala volumes with cortisol secretion in unipolar depressed patients - Anna Schuhmacher; Rainald Mössner; Frank Jessen; Lukas Scheef; Wolfgang Block; Anna Christine Belloche; Leonhard Lennertz; Hanne Welper; Susanne Höfels; Ute Pfeiffer; Michael Wagner; Wolfgang Maier; et al. (Psychiatry research : the official publication of the International Society for Neuroimaging in Psychiatry, 2012)

Dynorphins Regulate Fear Memory : from Mice to Men - A. Bilkei-Gorzo; S. Erk; B. Schurmann; D. Mauer; K. Michel; H. Boecker; L. Scheef; H. Walter; A. Zimmer (The journal of neuroscience : the official journal of the Society for Neuroscience, 2012)

Glucose metabolism, gray matter structure, and memory decline in subjective memory impairment - Lukas Scheef; Annika Spottke; Moritz Daerr; Alexius Joe; Nadine Striepens; Heike Kölsch; Julius Popp; Marcel Daamen; Dominik Gorris; Michael T. Heneka; Henning Boecker; Hans J. Biersack; et al. (Neurology : official journals of the American Academy of Neurology, 2012)

Interaction effects of subjective memory impairment and ApoE4 genotype on episodic memory and hippocampal volume - N. Striepens; L. Scheef; A. Wind; D. Meiberth; J. Popp; A. Spottke; H. Kölsch; M. Wagner; F. Jessen (Psychological medicine : a journal for research in psychiatry and the allied science, 2011)

Advocating neuroimaging studies of transmitter release in human physical exercise challenges studies - Henning Boecker; Ahmed Othman; Sarah Mueckter; Lukas Scheef; Max Pensel; Marcel Daamen; Jakob Jankowski; H. Schild; T. Tölle; M. Schreckenberger (Open Access Journal of Sports Medicine, 2010)

DNA sequence variants of the FKBP5 gene are associated with unipolar depression - Astrid Zobel; Anna Schuhmacher; Frank Jessen; Susanne Höfels; Olrik von Widdern; Martin Metten; Ute Pfeiffer; Claudia Hanses; Tim Becker; Marcella Rietschel; Lukas Scheef; Wolfgang Block; et al. (The International Journal of Neuropsychopharmacology : official scientific journal of the Collegium Internationale Neuro-Psychopharmacologicum (CINP), 2010)

Erfahrungen mit der MRT des Hirns bei Frühgeborenen : Hinweise auf Schädigung der weißen Substanz in T2- und Diffusionswichtung bei 3 Tesla - M. Born; L. Scheef; H. Boecker; A. Heep (Klinische Pädiatrie : clinical research and practice in pediatrics, 2010)
(Cerebral MRI of preterm neonates at term equivalent age at 3 Tesla : hints at white matter damage on T2- and diffusion weighted images)

Resting-State Perfusion in Nonmedicated Schizophrenic Patients : A Continuous Arterial Spin-labeling 3.0-T MR Study - Lukas Scheef; Christoph Manka; Marcel Daamen; Kai-Uwe Kühn; Wolfgang Maier; Hans H. Schild; Frank Jessen (Radiology : a monthly journal devoted to clinical radiology and allied sciences, 2010)

Visuospatial perspective taking in a dynamic environment : Perceiving moving objects from a first-person-perspective induces a disposition to act - H. Kockler; L. Scheef; R. Tepest; N. David; B.H. Bewernick; A. Newen; H.H. Schild; M. May; K. Vogeley (Consciousness and cognition : an international journal, 2010)

Volume Loss of the Medial Temporal Lobe Structures in Subjective Memory Impairment - Nadine Striepens; Lukas Scheef; Andrea Wind; Julius Popp; Annika Spottke; Déirdre Cooper-Mahkorn; Husam Suliman; Michael Wagner; Hans H. Schild; Frank Jessen (Dementia and Geriatric Cognitive Disorders, 2010)

A new MRI-compatible devive for passive sensorimotor stimulation in newborns - Dietrich Holz; Lukas Scheef; Henning Boecker; M Plein; M Drolshagen; Axel Heep (NeuroImage : a journal of brain function, 2009)
Organization for Human Brain Mapping 2009: annual Meeting ; 15. Juni 2009 in San Francisco

Distinct striatal regions for planning and executing novel and automated movement sequences - J. Jankowski; L. Scheef; C. Huppe; H. Boecker (NeuroImage : a journal of brain function, 2009)

Functional Magnetic Resonance Imaging of the Sensorimotor System in Preterm Infants - Axel Heep; Lukas Scheef; Jakob Jankowski; Mark Born; Nadine Zimmermann; Deborah Sival; Arie Bos; Jürgen Gieseke; Peter Bartmann; Hans Schild; Henning Boecker (Pediatrics : official journal of the American Academy of Pediatrics, 2009)

Multimodal motion processing in area V5/MT : Evidence from an artificial class of audio-visual events - Lukas Scheef; Henning Boecker; Marcel Daamen; Ursula Fehse; Martin W. Landsberg; Dirk-Oliver Granath; Heinz Mechling; Alfred O. Effenberg (Brain Research, 2009)

Neural correlates of semantic ambiguity processing during context verification - Klaus Hoenig; Lukas Scheef (NeuroImage : a journal of brain function, 2009)

No association of the Val66Met polymorphism of the brain-derived neurotrophic factor with hippocampal volume in major depression - Frank Jessen; Anna Schuhmacher; Ole von Widdern; Vera Guttenthaler; Susanne Hofels; Husam Suliman; Lukas Scheef; Wolfgang Block; Horst Urbach; Wolfgang Maier; Astrid Zobel (Psychiatric Genetics, 2009)

Smoking Tobacco and Collective Myopia - Christian G Schütz; Lukas Scheef; Amir A Sepehry (The Canadian journal of psychiatry : CJP, 2009)

The value of HMPAO SPECT in predicting treatment response to citalopram in patients with major depression - Holger Brockmann; Astrid Zobel; Alexius Joe; Kim Biermann; Lukas Scheef; Anna Schuhmacher; Olrik von Widdern; Martin Metten; Hans-Juergen Biersack; Wolfgang Maier; Henning Boecker (Psychiatry research : the official publication of the International Society for Neuroimaging in Psychiatry, 2009)

A role of the basal ganglia and midbrain nuclei for initiation of motor sequences - H. Boecker; J. Jankowski; P. Ditter; L. Scheef (NeuroImage : a journal of brain function, 2008)
The mesial premotor cortex is crucial for planning sequential procedures and movement initiation. With event-related (ER) functional magnetic resonance imaging (fMRI) it has been possible to separate mesial premotor activation before, during, and after self-initiated movements and, thereby, to distinguish advance planning from execution. The mesial premotor cortex is part of distributed cortico-basal ganglia-thalamo-cortical networks but, to date, the subcortical contributions to self-initiated movements are far less well understood. Using ER fMRI at 3T in 12 right-handed male volunteers, we studied the subcortical activation preceding an automated four-digit finger sequence that was either self-initiated or triggered externally by a visual cue. Beyond typical cortical activation increases in fronto-parietal regions, both initiation modes induced consistent subcortical activation in basal ganglia, midbrain (substantia nigra), and ipsilateral cerebellum. The planning phase of the internally initiated condition, when contrasted with the externally triggered condition, was associated with enhanced activity in frontal regions (mesial premotor cortex/rostral cingulate zone, dorsolateral prefrontal cortex), parietal regions (precuneus, inferior parietal cortex, encroaching onto V5/MT), insula, contralateral anterior putamen and midbrain (bilateral red nucleus/subthalamic nucleus). These data demonstrate the impact of initiation mode on planning-related activity in the ventral basal ganglia and interconnected midbrain nuclei, thereby stressing the crucial role of distributed cortico-basal ganglia-thalamo-cortical networks for self-initiated automated motor repertoires. Involvement of the substantia nigra during planning, as shown here, indicates dopaminergic gating of motor sequences.

Gegenwärtiger Stand der funktionellen MRT bei Neugeborenen und Kindern im ersten Lebensjahr - H. Boecker; L. Scheef; J. Jankowski; N. Zimmermann; M. Born; A. Heep (RöFo : Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2008)
Currently, a paradigm shift towards expanded early use of cranial MRI in newborns at risk and infants in the first year of life can be observed in neonatology. Beyond clinical MRI applications, there is progressive use of functional MRI (fMRI) in this age group. On the one hand, fMRI allows monitoring of functional developmental processes depending on maturational stage; on the other hand, this technique may provide the basis for early detection of pathophysiological processes as a prerequisite for functionally guided therapeutic interventions. This article provides a comprehensive review of current fMRI applications in neonates and infants during the first year of life and focuses on the associated methodological issues (e. g. signal physiology, sedation, safety aspects).

Hippocampal Surface Analysis in Subjective Memory Impairment, Mild Cognitive Impairment and Alzheimer’s Dementia - Ralf Tepest; Lei Wang; John G. Csernansky; Philip Neubert; Reinhard Heun; Lukas Scheef; Frank Jessen (Dementia and Geriatric Cognitive Disorders, 2008)
BACKGROUND/AIMS: Alzheimer's disease (AD) is preceded by prodromal states. To determine the neuroanatomical basis for the relationship among such states, we assessed surface conformations of the hippocampus in AD, mild cognitive impairment (MCI) and subjective memory impairment (SMI). METHODS: Hippocampal surfaces were reconstructed three-dimensionally via large-deformation high-dimensional MRI brain mapping in 14 SMI, 15 MCI, 12 AD and 13 controls. The surfaces were divided a priori into lateral, superior and inferior-medial zones, which approximated the CA1, combined CA2, CA3, CA4 subfields and the subiculum, respectively. RESULTS: Group differences reached statistical significance in the lateral zone (F = 3.2, d.f. = 3, p = 0.033) and inferior-medial zone (F = 2.8, d.f. = 3, p = 0.049) subfields. The groups differed in total hippocampal volume only at the trend level (F = 2.5, d.f. = 3, p = 0.071). Surface deformation maps revealed similar patterns in SMI, MCI and AD subjects, but quantitative differences were significant only when comparing MCI and AD with control subjects. CONCLUSIONS: Hippocampal surface deformation in the CA1 subfield was most pronounced in AD, less so in MCI and minor in SMI subjects. These results suggest that hippocampus degeneration develops gradually in AD, and may be observable long before dementia is apparent.

Interrelated neuropsychological and anatomical evidence of hippocampal pathology in the at-risk mental state - R. Hurlemann; F. Jessen; M. Wagner; I. Frommann; S. Ruhrmann; A. Brockhaus; H. Picker; L. Scheef; W. Block; H. H. Schild; W. Moller-Hartmann; B. Krug; et al. (Psychological Medicine : a journal for research in psychiatry and the allied science, 2008)
ACKGROUND: Verbal learning and memory deficits are frequent among patients with schizophrenia and correlate with reduced magnetic resonance imaging (MRI) volumes of the hippocampus in these patients. A crucial question is the extent to which interrelated structural-functional deficits of the hippocampus reflect a vulnerability to schizophrenia, as opposed to the disorder per se. METHOD: We combined brain structural measures and the Rey Auditory Verbal Learning Test (RAVLT) to assess hippocampal structure and function in 36 never-medicated individuals suspected to be in early (EPS) or late prodromal states (LPS) of schizophrenia relative to 30 healthy controls. RESULTS: Group comparisons revealed bilaterally reduced MRI hippocampal volumes in both EPS and LPS subjects. In LPS subjects but not in EPS subjects, these reductions were correlated with poorer performance in RAVLT delayed recall. CONCLUSIONS: Our findings suggest progressive and interrelated structural-functional pathology of the hippocampus, as prodromal symptoms and behaviours accumulate, and the level of risk for psychosis increases. Given the inverse correlation of learning and memory deficits with social and vocational functioning in established schizophrenia, our findings substantiate the rationale for developing preventive treatment strategies that maintain cognitive capacities in the at-risk mental state.

Unipolar depression and hippocampal volume: Impact of DNA sequence variants of the glucocorticoid receptor gene - Astrid Zobel; Frank Jessen; Olrik von Widdern; Anna Schuhmacher; Susanne Höfels; Martin Metten; Marcella Rietschel; Lukas Scheef; Wolfgang Block; Tim Becker; Hans H. Schild; Wolfgang Maier; et al. (American Journal of Medical Genetics : Part B ; Neuropsychiatric Genetics, 2008)
Glucocorticoid receptor (GR) plays a major role in regulation of the hypothalamic-pituitary-adrenocortical (HPA) system; HPA dysregulation represents the most consistent biological pattern of depression. Multiple functional polymorphisms are known for the GR gene, which might influence the development of unipolar depression. Previous studies reported associations to some variants in this gene but not consistently so. We investigated seven genetic polymorphisms in the GR gene (NR3C1) located in the putative promoter, exon 2 and intron 2 region. Study populations were 322 German inpatients with recurrent unipolar depression, and 298 German controls recruited from the general population. The relationships between intermediate phenotypes (hippocampal and amygdala volumes) and NR3C1 DNA sequence variants were additionally explored in a subpopulation of patients. We found association between the diagnosis of depression and DNA sequence variants in intron 2 as well as in the 5' region of the NR3C1 gene but not for the previously studied exon 2 and putative promoter variants (global test after control of multiple testing, P = 0.02). In patients, diagnosis-related alleles were also associated to hippocampal volume reduction and amygdala volume variation. Unipolar depression is associated with DNA variants of the NR3C1 gene in our population. Neurobiological underpinnings of depression as volumetric reductions of the hippocampus may also be mediated by variants in this gene.

Methodische Aspekte der funktionellen Neurobildgebung im MRT-Hochfeldbereich : eine kritische Übersicht - L. Scheef; M. Landsberg; H. Boecker (RöFo : Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2007)
(Methodological aspects of functional neuroimaging at high field strength: a critical review) The last few years have proven that high field magnetic resonance imaging (MRI) is superior in nearly every way to conventional equipment up to 1.5 tesla (T). Following the global success of 3T-scanners in research institutes and medical practices, a new generation of MRI devices with field strengths of 7T and higher is now on the horizon. The introduction of ultra high fields has brought MRI technology closer to the physical limitations and increasingly greater costs are required to achieve this goal. This article provides a critical overview of the advantages and problems of functional neuroimaging using ultra high field strengths. This review is principally limited to T2*-based functional imaging techniques not dependent on contrast agents. The main issues include the significance of high field technology with respect to SNR, CNR, resolution, and sequences, as well as artifacts, noise exposure, and SAR. Of great relevance is the discussion of parallel imaging, which will presumably determine the further development of high and ultra high field strengths. Finally, the importance of high field strengths for functional neuroimaging is explained by selected publications.

Supramodal language comprehension : Role of the left temporal lobe for listening and reading - Robert Lindenberg; Lukas Scheef (Neuropsychologia : an international journal in behavioural and cognitive neuroscience, 2007)
In this fMRI study, we aimed at identifying the cortical areas engaged in supramodal processing of language comprehension. BOLD changes were recorded in 19 healthy right-handed subjects reading or listening to a story. During the visual control tasks the volunteers attended to a series of continuous letterstrings or a fixation cross, while during the acoustic control tasks either a reversed text or white noise were presented. The conjunction of the visual and acoustic story processing yielded left-dominant activations which in comparison to language-like stimuli focused to the left middle temporal gyrus as well as to the supramarginal gyrus. We conclude that the core structure representing supramodal language comprehension is the left temporal lobe at both banks of the superior temporal sulcus.

Volume reduction of the entorhinal cortex in subjective memory impairment - Frank Jessen; Ludger Feyen; Katrin Freymann; Ralf Tepest; Wolfgang Maier; Reinhard Heun; Hans-H. Schild; Lukas Scheef (Neurobiology of Aging : experimental and clinical research, 2006)
To examine the biological basis of subjective memory impairment (SMI), defined as the feeling of memory worsening with normal memory performance, we measured the volume of the entorhinal cortex (EC) and the hippocampus in SMI subjects, patients with mild cognitive impairment (MCI), patients with Alzheimer's disease (AD) and healthy controls (CO). Compared with controls, the EC was smaller in the SMI group (left: p=0.060; right: p=0.045) and in the other two groups in the following order: CO>SMI>MCI>AD. The same sequence was observed with regard to hippocampal volumes, but the volume reduction of the left hippocampus in the SMI group only reached a trend towards significance (p=0.072) and the right was not significantly smaller compared with controls (p=0.37). Compared with controls the average (left/right) volume reduction of the EC was 18% (SMI), 26% (MCI) and 44% (AD). The mean volume reduction of the hippocampus was 6% (SMI), 16% (MCI) and 19% (AD). Our results mirror the temporal sequence of neurodegeneration in AD and support the concept of SMI as the first clinical manifestation of dementia.

Functional 3.0-T MR Assessment of Higher Cognitive Function : Are there advantages over 1.5-T imaging? - Klaus Hoenig; Christiane K. Kuhl; Lukas Scheef (Radiology : a monthly journal devoted to clinical radiology and allied sciences, 2005)
PURPOSE: To compare cortical activation patterns associated with manual motor decision tasks at 1.5- and 3.0-T functional magnetic resonance (MR) imaging. MATERIALS AND METHODS: The local ethics committee approved this study, and informed written consent was obtained. Ten right-handed healthy volunteers (eight men and two women; mean age, 35 years +/- 7 [standard deviation]) underwent functional MR imaging twice, once at 1.5 T and once at 3.0 T, while performing cognitive tasks that demanded manual motor decisions (letter-finger matching and lexical and semantic decisions). While stimulus presentation was blocked, an event-related model was employed to analyze subjects' individual responses. A group analysis of functional data was performed with a t test of 1.5- and 3.0-T results in the 10 subjects. RESULTS: Manual motor decisions activated a widespread network of motor- (primary motor, posterior parietal) and decision-related areas (superior frontal cortex or anterior cingulate) at both field strengths (P <.05, corrected). Moreover, additional functional activation was detected in medial (supplementary motor area) and dorsal premotor regions (P <.05, corrected) at 3.0-T functional MR imaging, which was not detectable with corresponding 1.5-T imaging. The mean t value for peak voxels in activated areas detectable with both systems was 1.3 times larger at 3.0 T than that at 1.5 T. CONCLUSION: Functional 3.0-T MR imaging allows detection of additional activation in cortical areas involved in higher executive motor functions compared with functional 1.5-T MR imaging.

Mediotemporal contributions to semantic processing : fMRI evidence from ambiguity processing during semantic context verification - Klaus Hoenig; Lukas Scheef (Hippocampus, 2005)
The medial temporal lobe (MTL) is well known to be crucial for various types of memory; however, controversy remains as to which of its substructures contribute to semantic processing and, if so, to what extent. The current study addresses the issue of MTL contributions to semantic processing during lexico-semantic ambiguity processing by using functional magnetic resonance imaging (fMRI) in combination with a context verification task (CVT). The CVT required decisions on the semantic fit of congruent and incongruent target words to the overall meaning of preceding sentential contexts with and without semantic ambiguity. In two of the four experimental conditions (congruent homographic, incongruent homographic), target decisions were critically dependent on the successful processing of prior sentence-final lexico-semantic ambiguity. Semantic context verification per se evidenced bilateral activations of the hippocampus that were part of a functional network including inferior prefrontal and superior parietal cortices. Commonalities in activation differences pertaining to the specific cognitive component of lexico-semantic ambiguity processing were found in a left temporal lobe network that comprised activation foci in the temporal pole, the parahippocampal and fusiform gyri. The present results suggest that the hippocampus may well contribute to semantic processing, namely by a mnemonic function that serves to link the target meaning representation with the meaning of a prior sentence context. Contrary to previous reports from human lesion studies, the present findings further suggest, that the specific cognitive component of lexico-semantic ambiguity processing is neither dependent on the hippocampus nor exclusively subserved by the temporal pole, but also recruits an associative semantic memory function from the parahippocampal gyrus as well as a more general (bottom-up) semantic function from the fusiform gyrus.

Reduced Hippocampal Activation During Encoding and Recognition of Words in Schizophrenia Patients - Frank Jessen; Lukas Scheef; Lars Germeshausen; Youlha Tawo; Martin Kockler; Kai-Uwe Kuhn; Wolfgang Maier; Hans H. Schild; Reinhard Heun (American Journal of Psychiatry : official journal of the American Psychiatric Association, 2003)
OBJECTIVE: In patients with schizophrenia, impaired hippocampal activation either during encoding or recognition tasks has been observed in a few functional imaging experiments. In this fMRI study, the authors report results of word encoding and recognition in schizophrenia patients and healthy comparison subjects, with a special focus on correcting for behavioral recognition success in order to prevent a bias related to lower task performance in the schizophrenia patients. METHOD: The verbal encoding and recognition tasks were both first analyzed irrespective of recognition success. In a second analysis, recognition success was included in the block-designed encoding task as a covariate of no interest, and incorrectly classified items were rejected from the analysis of the event-related recognition task. RESULTS: Patients performed poorer on the recognition task than the comparison subjects. Bilateral hippocampal activation during encoding and recognition was observed in both groups. Right hippocampal activation in patients during recognition became significant only after exclusion of wrongly classified items. Group comparison revealed greater activation in the healthy comparison subjects in the left anterior hippocampus during encoding and bilaterally during recognition. Greater bilateral hippocampal activation in the healthy subjects and greater activation in the right anterior hippocampus in the schizophrenic patients were revealed after presentation of novel words, which were intermixed with previously encoded words in the recognition task. After exclusion of incorrectly classified items, the differences in the right hippocampus remained significant. CONCLUSIONS: This study provides evidence for disturbed hippocampal function during verbal encoding and recognition in patients with schizophrenia. It extends previous studies by correcting for the possible confound of differences in behavioral task performance. This approach further supports the concept of hippocampal dysfunction in schizophrenia.

Novelty detection and repetition suppression in a passive picture viewing task : A possible approach for the evaluation of neuropsychiatric disorders - Frank Jessen; Christoph Manka; Lukas Scheef; Dirk‐Oliver Granath; Hans H. Schild; Reinhard Heun (Human Brain Mapping, 2002)
The applicability of functional magnetic resonance imaging (fMRI) in patients with Alzheimer's disease (AD) or schizophrenia is frequently limited by cognitive impairment, which prevents the adequate execution of complex tasks. An experimental design that puts only minor demands on the patients' cognitive ability but engages disease-relevant brain structures would be of benefit. Novelty detection and repetition suppression are two basic components of memory that might be used to investigate specific brain areas under these conditions. Novelty detection has been related to hippocampal activation increases. Stimulus repetition related activation decreases (suppression) have been observed in the extrastriate cortex and have been related to perceptual priming. Both processes have been examined primarily in neuroimaging studies with complex cognitive tasks. We used event-related fMRI to investigate novelty- and repetition-related effects in an attended but passive picture-viewing task in healthy subjects. The differential activation, detected in the novel vs. repeated contrast, was located in the bilateral anterior hippocampus and in bilateral occipital and inferior-temporal areas. The hippocampal activation is of interest because medial temporal lobe lesions are key features in AD and schizophrenia. The repetition-related activation decreases in the extrastriate areas are of potential value in investigating the conflicting results regarding perceptual priming impairment in both disorders. Our results indicate that activation of disease-relevant brain regions under passive task conditions is possible. This might increase the utility of functional imaging in cognitively impaired patients.

Encoding and retrieval related cerebral activation in continuous verbal recognition - Frank Jessen; Sebastian Flacke; Dirk-Oliver Granath; Christoph Manka; Lukas Scheef; Andreas Papassotiropoulos; Hans H. Schild; Reinhard Heun (Brain research : Cognitive brain research, 2001)
The differential neuronal activation related to encoding of novel and recognition of previously studied items and the effect of retrieval effort on neuronal activation were assessed in a event-related functional magnetic resonance imaging experiment. A verbal continuous recognition task with two repetitions of the target items was used. The interpretation of the results was focused on brain areas that have been previously reported to be involved in explicit memory. Encoding of novel words in comparison with the first repetition was associated with a stronger activation in the left parahippocampal and inferior frontal gyrus. Encoding of novel words compared to the second repetition was related to a greater bifrontal activation. Recognition of studied items was associated with greater activation in the medial and bilateral inferior parietal lobe at first repetition and in the medial and left inferior parietal lobe at second repetition in comparison with encoding of the novel items. Recognition at first repetition compared to recognition at second repetition was associated with greater bilateral frontal activation. The results are discussed in relation to current concepts of spatial differentiation of memory function and findings from event-related potentials studies of continuous recognition.

Verbesserte Diagnostik des frühen Hirninfarktes durch den kombinierten Einsatz von Diffusions- und Perfusionsbildgebung - S. Flacke; E. Keller; A. Hartmann; P. Mürtz; J. Textor; H. Urbach; P. Folkers; F. Träber; J. Gieseke; W. Block; L. Scheef; C. Leutner; et al. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 1998)
(Improved diagnosis of early cerebral infarct by the combined use of diffusion and perfusion) PURPOSE: To evaluate the feasibility and the diagnostic efficacy of multislice diffusion-weighted and perfusion imaging in addition to FLAIR-TSE, T2w-GraSE and MR-angiography in the diagnosis of acute stroke. METHODS: 18 patients with acute stroke were examined at 1.5 Tesla (Gyroscan ACS-NT, Philips Medical Systems) within 6 (n = 9) and 6-48 (n = 9) hours, respectively, and followed at regular intervals. For diffusion imaging we used a multislice multishot EPI-SE sequence with navigator echo correction and cardiac gating. Perfusion imaging was done by means of a FFE-EPI sequence after bolus injection of Gd-DTPA. RESULTS: The diagnostic value of diffusion-weighted and perfusion imaging was significantly higher compared with FLAIR-TSE (p = 0.0023) and GraSE (p = 0.0012) during the first 6 hours. With FLAIR-TSE and GraSE first pathologic changes were seen after 4 hours. We detected perfusion deficit (rCBV < 10%) and a corresponding drop of the ADC in all infarcts larger than 1 cm in diameter. Within the area of low rCBV the combined analysis of diffusion and perfusion imaging allows to identify an infarct region with characteristics of a penumbra and one with characteristics of the infarct core. TTP was increased in the surrounding tissue. However, parts of this area were rarely included in the infarct. The final extension of the untreated infarct, as revealed by computed tomography, corresponded well to the perfusion deficit. CONCLUSIONS: Early ischaemic cerebral infarcts can be diagnosed with diffusion and perfusion imaging before pathological changes are visualized with other imaging modalities. The combined use may allow to distinguish the infarct core from surrounding, potentially salvageable tissue.